2007
DOI: 10.1261/rna.601507
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor G stabilizes the hybrid-state conformation of the 70S ribosome

Abstract: Following peptide bond formation, transfer RNAs (tRNAs) and messenger RNA (mRNA) are translocated through the ribosome, a process catalyzed by elongation factor EF-G. Here, we have used a combination of chemical footprinting, peptidyl transferase activity assays, and mRNA toeprinting to monitor the effects of EF-G on the positions of tRNA and mRNA relative to the A, P, and E sites of the ribosome in the presence of GTP, GDP, GDPNP, and fusidic acid. Chemical footprinting experiments show that binding of EF-G i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
135
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 41 publications
15
135
1
Order By: Relevance
“…Conversely, a method for objectively probing both the entrance and exit sites of the mRNA with single-nt resolution is necessary and has not been reported in the literature. For example, the toe-printing assay uses a reserve transcriptase primed at the 3ʹ-distal end to transcribe the mRNA toward the ribosome [6]. The residue at the 3ʹ end of the mRNA exiting the ribosome is deduced by the cDNA length that was limited by the clash between the reserve transcriptase and the ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a method for objectively probing both the entrance and exit sites of the mRNA with single-nt resolution is necessary and has not been reported in the literature. For example, the toe-printing assay uses a reserve transcriptase primed at the 3ʹ-distal end to transcribe the mRNA toward the ribosome [6]. The residue at the 3ʹ end of the mRNA exiting the ribosome is deduced by the cDNA length that was limited by the clash between the reserve transcriptase and the ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of EF-G, tRNAs fluctuate between the classical and hybrid states (10)(11)(12); however, these fluctuations do not result in productive translocation of mRNA and tRNAs on the small ribosomal subunit. EF-G·GTP binding was shown to transiently stabilize the rotated, hybrid state conformation (2,(12)(13)(14)(15)(16)(17) and catalyze mRNA and tRNA translocation during the reverse rotation of the small subunit (16,18) (Fig. 1A).…”
mentioning
confidence: 99%
“…Then, Cy5-labeled EF-G was flowed into the slide in the presence of GTP and fusidic acid (Fus), an antibiotic which does not interfere with one round of translocation or GTP hydrolysis, but instead inhibits EF-G release after GTP hydrolysis (35). Under these experimental conditions, dipeptidyl and deacylated tRNAs rapidly (5-20 s −1 ) translocate from the A and P to the P and E sites, respectively, and EF-G·GDP·Fus becomes bound to the posttranslocation ribosome (15,16), which was previously shown to be fixed in the nonrotated conformation (17). We used Fus to extend EF-G residence time on the ribosome because in the absence of Fus (with GTP alone), EF-G binds and rapidly dissociates from the ribosome (dwell time 100-350 ms) (18).…”
mentioning
confidence: 99%
“…The observation of such a rotation was confirmed in the studies by H. F. Noller's group using a cross-linking technique, fluorescence resonance energy transfer (FRET) methodology, and "translation-libration-screw" (TLS) crystallographic refinement (66 -68). The ribosome was shown to be fixed (locked) in the rotated form upon binding of elongation factor (EF)-G, the catalyst of translocation, until EF-G and deacylated tRNA were released from the ribosome (64,69). More recently, using single-molecule FRET methodology, it was found that ribosomes undergo spontaneous intersubunit movements oscillating between the original ("classical") and rotated forms, with the equilibrium shifted toward either the original or rotated forms depending on the functional state of the ribosome (70).…”
Section: Conformational Movements In Translating Ribosomementioning
confidence: 99%
“…Thus, it seems that the spontaneous shift of the acceptor ends of the product tRNA residues and the appearance of the hybrid state after transpeptidation are allowed because of establishment of the locking-unlocking equilibrium (step 1). Indeed, cryoelectron microscopy studies and chemical footprinting and FRET analyses showed that the hybrid situation correlates with the rotated state of the ribosome (65,67,69,70). It is remarkable that binding of EF-G with a non-cleavable GTP analogue (that is EF-G with GTP prior to GTP hydrolysis) was shown to fix the rotated state of the ribosome and the hybrid positions of peptidyl-tRNA and deacylated tRNA ("locking of the unlocked state of the ribosome") (step 2, position III).…”
Section: Stepwise Conveyance Of Trna and Mrna Through The Translatingmentioning
confidence: 99%